Normalized difference vegetation index for rice management in El Espinal, Colombia (2018)
Aerial images and the Normalized Difference Vegetation Index (NDVI) of the stage after panicle initiation were evaluated as tools that help large-scale rice monitoring and decision-making that favors crop profitability. NDVI was used to identify problems in the development and growth of FEDEARROZ-2000. FEDEARROZ-2000 is a variety of rice, which is resistant to the “hoja blanca” virus and direct “sogata” damage that affect fields in tropical America. The temporal dynamics of the NDVI for FEDEARROZ-2000 were estimated. An NDVI lower than 0.8 in the Stage of Rice Panicle Development (SRPD) was related to areas with levelling problems, differences in the vegetative stage, water stress, and spacing between plants. The NDVI for the SRPD had a significant positive correlation with yield, 1,000 grain weight and the number of panicles (Pearson's R≥0.86; probability value P ≤0.04). NDVI mapping at milky stage helped to identify production environments and to schedule the harvest areas. Keywords: NDVI; rice; unmanned aerial vehicle